Influence of silica content on liquid phase sintering of silicon carbide with yttrium-aluminum garnet - Kim, YW; Mitomo, M; Lee, JG (CERAMIC SOC JAPAN-NIPPON SERAMIKKUSU KYOKAI, 1996)
Densification of SiC with oxide additives is affected mainly bg the amounts of free C and SiO2 contained in the starting powders. In this study, the influence of oxidation of starting powders on densification was investigated. Oxidation of SiC powders, prior to liquid phase sintering, increased the oxygen content and decreased the carbon content remarkably, and led to higher sintered density for both alpha- and beta-Sic. Higher sintered density was attributed to the formation of liquid at lower temperatures and the suppression of reactions between the free C and oxide additives.
Keywords: FRACTURE-TOUGHNESS; MICROSTRUCTURE